Why do people choose courts to resolve disputes? A fuzzy-set analysis of Chinese citizens’ judicial reliance - Wang, Xiang; Guo, Changwei; Lyu, Yuwen; Zhu, Shouchao (Frontiers in Psychology, 2023)
We use the concept of judicial reliance to describe the willingness and extent to which citizens seek the help of the court in a dispute. There are obvious local differences in the degree of judicial reliance in different provinces, with some citizens more willing to resort to the courts to settle disputes, whereas others are indifferent to the courts. Based on the judicial survey data of 31 provinces in China, we use fuzzy-set qualitative comparative analysis to explore the possible reasons for differences in citizens’ judicial reliance in China. We find that citizens’ judicial reliance is deeply influenced and restricted by five judicial conditions: transparency, corruption, independence, procedure, and professionalism. These causal conditions influence and interact with each other, thus forming six configurations that produce high judicial reliance. Among these six configurations, judicial professionalism is always the core condition. In recent years, China has indeed attached great importance to the construction of judicial professionalism, which not only optimizes the quality of the internal personnel of the court but also strengthens the public’s recognition of the court.